MOBILE BANKING AND DIGITAL WALLETS AS CATALYSTS FOR FINANCIAL ACCESS AMONG NIGERIAN RURAL ENTREPRENEURS (UNIZIK Journal of Marketing, 2026)
Access to formal financial services remains uneven in many developing economies, particularly among rural entrepreneurs in Nigeria who continue to experience limited integration into the formal financial system despite the expansion of digital finance platforms. Mobile banking and digital wallets have increasingly been promoted as accessible and cost-effective alternatives to traditional banking channels. However, evidence suggests that adoption and sustained usage in rural areas remain constrained by infrastructural deficiencies, usability concerns, and limited perceived value. This study examined the relationship between mobile banking, digital wallet usage, and financial inclusion among rural entrepreneurs in Nigeria. A quantitative research design was adopted, and data were collected through a structured questionnaire administered to 363 rural entrepreneurs across Kogi, Kwara, Nasarawa, and Niger States. Descriptive statistics and regression analysis were employed to test hypotheses relating to infrastructure, ease of use, transaction usage, and perceived usefulness. The descriptive findings revealed generally low to moderate mean scores for ease of use, perceived usefulness, continued use intention, and digital wallet usage, indicating that respondents still experience substantial barriers in the adoption and utilization of digital financial services.
Keywords: Mobile banking, Digital wallets, Financial inclusion, Rural entrepreneurs, Perceived usefulness, Financial infrastructure